2021
DOI: 10.1021/acschembio.1c00027
|View full text |Cite
|
Sign up to set email alerts
|

Cysteine Hydropersulfide Inactivates β-Lactam Antibiotics with Formation of Ring-Opened Carbothioic S-Acids in Bacteria

Abstract: Hydrogen sulfide (H2S) formed during sulfur metabolism in bacteria has been implicated in the development of intrinsic resistance to antibacterial agents. Despite the conversion of H2S to hydropersulfides greatly enhancing the biochemical properties of H2S such as antioxidant activity, the effects of hydropersulfides on antibiotic resistance have remained unknown. In this work, we investigated the effects of H2S alone or together with cystine to form cysteine hydropersulfide (CysSSH) on the activities of antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…A new mode of antibiotic resistance mediated by sulfide was reported in pathogenic bacteria that involves inhibition of the oxidative stress imposed by ROS-generating antibiotics. Several studies described that the genes encoding H 2 S-releasing enzymes, such as CBS and CSE, in B. anthracis , P. aeruginosa , S. aureus , and M. tuberculosis, or 3-MST in E. coli , contribute to tolerance to gentamicin, ampicillin and nalidixic acid [ 31 , 33 ].…”
Section: H 2 S and Microbial Antibiotic Resistancementioning
confidence: 99%
“…A new mode of antibiotic resistance mediated by sulfide was reported in pathogenic bacteria that involves inhibition of the oxidative stress imposed by ROS-generating antibiotics. Several studies described that the genes encoding H 2 S-releasing enzymes, such as CBS and CSE, in B. anthracis , P. aeruginosa , S. aureus , and M. tuberculosis, or 3-MST in E. coli , contribute to tolerance to gentamicin, ampicillin and nalidixic acid [ 31 , 33 ].…”
Section: H 2 S and Microbial Antibiotic Resistancementioning
confidence: 99%
“…Recent studies also suggested that reactive sulfur species can have potent anti-inflammatory activity in cells and in vivo ( 45 , 48 , 49 ). In bacteria, persulfides and polysulfides offer protection from external bactericidal insults caused by immune cell responses and antibiotics ( 29 , 36 ). Thus, bacteria-specific persulfide-producing machinery may become an attractive target for development of antibacterial drugs ( 29 , 36 ).…”
Section: Introductionmentioning
confidence: 99%
“…These cytoprotective properties attributed to H 2 S may well be the result of downstream, more oxidized sulfur species, collectively termed reactive sulfur species (RSS) [ 8 ]. One of these RSS is the organic persulfide (RSSH), which has enhanced nucleophilicity compared to its thiol counterpart and readily reacts with infection-relevant oxidants and β-lactam antibiotics [ 8 , 9 , 10 , 11 ]. Although much of the work on RSS has focused on mammalian systems [ 8 ], RSS biogenesis has been shown to be present in a number of bacteria [ 7 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%